Sphingolipid metabolism and signaling in cardiovascular diseases - Borodzicz-Jażdżyk, Sonia; Jażdżyk, Piotr; Łysik, Wojciech; Cudnoch-Jȩdrzejewska, Agnieszka; Czarzasta, Katarzyna (Frontiers in Cardiovascular Medicine, 2022)
Sphingolipids are a structural component of cell membranes, derived from amino alcohol sphingosine. Its sphingoid base undergoes various types of enzymatic transformations that lead to the formation of biologically active compounds, which have a crucial role in essential pathways of cellular signaling, proliferation, maturation and death. The constantly growing number of experimental and clinical studies emphasizes the pivotal role of sphingolipids in the pathophysiology of cardiovascular diseases, including in particular ischemic heart disease, hypertension, heart failure and stroke. It has also been proven, that altering of the sphingolipid metabolism has cardioprotective properties in cardiac pathologies, including myocardial infarction. Recent studies suggest that selected sphingolipids may serve as valuable biomarkers useful in the prognosis of cardiovascular disorders in a clinical practice. This review aims to provide an overview of current knowledge about sphingolipid metabolism and signaling in cardiovascular diseases.